1985
DOI: 10.1073/pnas.82.24.8701
|View full text |Cite
|
Sign up to set email alerts
|

Independent segregation of two antigenic specificities (VP3 and VP7) involved in neutralization of rotavirus infectivity.

Abstract: Antiserum prepared against the M37 strain of rotavirus, recovered from an asymptomatic newborn infant in Venezuela, neutralized two prototype human rotaviruses that define two separate serotypes: serotype 1 (Wa) and serotype 4 (ST3). Thus, the M37 strain is a naturally occurring intertypic rotavirus. Analysis of reassortant viruses produced during coinfection in vitro indicated that the observed dual serotype specificity of M37 resulted from sharing a related outer (1-3).The genome of rotaviruses consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
218
0
7

Year Published

1986
1986
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(233 citation statements)
references
References 22 publications
8
218
0
7
Order By: Relevance
“…We have previously considered these isolates to be similar or identical to the St. Thomas 3 strain based on our observations that antiserum to one of them (FH4453) neutralizes the St. Thomas 3 strain. However, this does not eliminate the possibility that they represent naturally occurring intertypic strains as described by Hoshino et al (1985b) and we intend to investigate them further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously considered these isolates to be similar or identical to the St. Thomas 3 strain based on our observations that antiserum to one of them (FH4453) neutralizes the St. Thomas 3 strain. However, this does not eliminate the possibility that they represent naturally occurring intertypic strains as described by Hoshino et al (1985b) and we intend to investigate them further.…”
Section: Discussionmentioning
confidence: 99%
“…It was not until the successful adaptation of HRV to growth in cell culture (Sato et al, 1981;Urasawa et al, 1981) that an appropriate definition of subgroup and serotype was reported and neutralization assays enabling distinction of individual serotypes were developed (Wyatt et al, 1982;Beards & Flewett, 1984). While gene-coding assignment has previously revealed that the antigenic determinant responsible for subgroup is coded for by gene 6 and that gene 8 or 9, depending on the strain, codes for the serotype-specific determinant Greenberg et al, 1983) more recent information suggests that a further polypeptide, VP3, which is coded by gene 4, may also play a role in serotype specificity (Hoshino et al, 1985b;Offit & Blavat, 1986). The subgroup determinant is located on a 41000 tool.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Rotavirus has two outer capsid proteins, VP7 and VP4, which are independent neutralization antigens [19]. Serotype specificity of rotaviruses is ascribed mainly to the antigenic identity of VP7.…”
mentioning
confidence: 99%
“…Group A rotavirus classification based on neutralizing VP7 antigens is termed G-type (since VP7 is a glycoprotein), and VP4 neutralizing antigens is termed P-type (since VP4 is a protease sensitive protein). Genes that encode VP7 and VP4 can segregate separately, resulting in a large amount of antigenic diversity [42,88]. So far, 23 G-types and 32 P-types of rotavirus have been reported (Tables 1, 2) [24,57,94].…”
Section: Rotaviruses: Molecular Structure and Genotypesmentioning
confidence: 99%